Exploring intergenerational, intra-generational and transnational patterns of family caring in minority ethnic communities: the example of England and Wales - Vanessa Burholt (International Journal of Care and Caring, 2019)
We investigated family caring using established questions from national surveys of 1,206 adults aged 40+ from six minority ethnic communities in England and Wales. We included in our analysis factors that predisposed caring (age, sex, marital status and household composition) and enabled caring (health, material resources, education, employment and cultural values). In the general population, 15% of adults are family carers. Three groups reported lower levels of caring (Black African [12%], Chinese [11%] and Black Caribbean [9%]) and three reported higher levels of caring (Indian [23%], Pakistani [17%] and Bangladeshi [18%]). However, ethnicity predicted caring independent of other factors only for the Indian group.